Scaling climate resilience in Ghana's savannah maize belt: Leveraging smart production, soil technologies, and capacity strengthening - Amankwaa-Yeboah, Patricia; Ofosu-ampong, Kingsley; Masoud, Jalaludeen; Akpatsu, Isaac Boatey; Yeboah, Stephen; Jizorkuwie, Abdul-latif Baamonyor; Kyerematen, A.A; Abera, Wuletawu (2024)
Accounting for 50-60% of the country's cereal production, maize is extensively cultivated across all six agroecological zones, standing second only to cocoa in economic importance. Despite its significance, maize production in the Guinea Savannah zone, which spans nearly half of Ghana's land area, faces numerous challenges. These include unpredictable weather patterns characterized by droughts and floods, soil degradation due to inadequate conservation practices, limited access to mechanization, and insufficient utilization of agroadvisories. Such factors collectively hinder efficient land preparation, planting, and harvesting, leading to increased labor costs, reduced productivity, and decreased resilience to climate change. In response to these challenges, AICCRA, as part of its drive to promote climate-smart agriculture (CSA) and one health, rolled out improved soil and production technologies. These activities were led by the Alliance Bioversty and CIAT in collaboration with the CSIR-Crops Research Institute and the Department of Agriculture of the Kumbungu District. The primary goal of this initiative was to enhance crop resilience and productivity through the evaluation and implementation of smart production and soil packages. These packages integrated three key components: agroadvisories, which provide farmers with timely and location-specific advice on weather, soil moisture, and pest/disease management; good agronomic practices; and essential crop production equipment, particularly simple mechanization tools. The initiative employed a standardized methodology to ensure consistency and reliability in data collection and analysis. Key activities included field demonstrations to showcase the integrated smart production and soil packages, comprehensive capacity-building programs for farmers and extension agents, and rigorous data collection to assess the effectiveness of the implemented packages. The use of agroadvisories was pivotal, as they offered farmers critical guidance on weather management, optimizing water use, and planning field-based activities, thereby reducing crop losses and enhancing yields. Additionally, agroadvisories facilitated proactive pest and disease management, minimizing crop damage and the reliance on chemical pesticides and fertilizers. Stakeholder engagement was a crucial aspect of this initiative. By organizing field days and other collaborative events, the project successfully involved government agencies, research institutions, NGOs, and the private sector. These engagements not only fostered collaboration and support for sustainable agricultural initiatives but also exposed a wider audience to the innovative technologies being implemented. The project also focused on promoting the widespread adoption and scaling of smart production practices across the agroecological zone, thereby enhancing agricultural productivity and sustainability. The capacity-building efforts provided comprehensive training and support to smallholder farmers and agricultural stakeholders on the use of agroadvisories, mechanization equipment, and sustainable agricultural practices. This holistic approach laid the groundwork for a comprehensive understanding of the potential benefits of smart production and soil packages in the Guinea Savannah zone. The findings from this research are expected to inform evidence-based decision-making and contribute to the development of sustainable agricultural practices in Ghana, ultimately supporting the livelihoods of smallholder farmers and boosting the national economy.